Pemanfaatan Komunikasi Inovasi Digital Pertanian Perkotaan di Masa Pandemi Covid-19 - Leonard Dharmawan; Pudji Muljono; Dwi Retno Hapsari; Bagus Priyo Purwanto (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluhan Pembangunan Indonesia), 2023)
Communication of innovation in agriculture is a way for farmers not only to seek information about agriculture in an innovative way but also how to explore and share information with fellow farmers in an innovative way to increase their agricultural productivity. During the pandemic, due to restrictions on gatherings, counseling is carried out in an innovative way, namely digital. The purpose of this study was to determine the readiness of extension workers and supporting facilities for digital agriculture and extension, to determine the factors that influence the level of empowerment of farmers in the city of Bogor. This study uses quantitative research methods which are strengthened by qualitative data. The location of the research was determined deliberately in the city of Bogor, which has good urban agriculture. The results show that extension workers are ready to face digital counseling and the communication support facilities for digital innovation in the city of Bogor are good for digital counseling. the level of empowerment of farmers directly affects the productivity of farmers and indirectly positively influenced by; environmental support, farmer innovation activities, and individual characteristics of farmers.